Criticism of Religious Literature on the Novel Maryam by Okky Madasari - Hermalinda Rizki Pratiwi; Trie Utari Dewi (Universitas Indraprasta PGRI, 2022)
The purpose of this study was to determine the religious values contained in the novel and religious literary criticism of the novel Maryam. This study uses a qualitative method. By describing the data in the form of an analysis of religious values in the novel Maryam. The object of this research is the novel Maryam by Okky Madasari. Data collection techniques used are literature study techniques and analytical techniques. The data analysis technique used is to categorize each paragraph that is included in religious values based on the theory of Heri Jauhari (2010). There are three criticisms in this novel based on Heri Jauhari's theory, namely the monotheistic aspect, the fiqh aspect, and the moral aspect. The criticism obtained on the aspect of monotheism is found in the attitude of Maryam who chose to leave her faith. The criticism obtained on the fiqh aspect is in Umar's response when he had sexual relations with Komang. The criticism obtained on the moral aspect of this novel is in the treatment of discrimination against residents who adhere to Ahmadiyah.Keywords: Literary criticism; religiosity; novel Maryam.